2021
DOI: 10.35295/osls.iisl/0000-0000-0000-1213
|View full text |Cite
|
Sign up to set email alerts
|

Image Based Sexual Abuse proclivity and victim blaming

Abstract: Image Based Sexual Abuse (IBSA) denotes the creation, distribution, and/or threat of distribution of intimate images of another person online without their consent. The present study aims to extend emerging research on perpetration of IBSA with the development and preliminary validation for the moral disengagement in IBSA scale, while also examining the role of the dark triad, sadism, and sexism in a person’s likelihood to perpetrate IBSA. One hundred and twenty English speaking participants (76 women, 44 men;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 44 publications
1
7
0
2
Order By: Relevance
“…Finally, the results showed that the victims’ perception of violation of the law was higher among middle students than both the biennium and triennium students, consistent with greater use among younger adolescents of moral disengagement mechanisms, such as victim-blaming, resulting in greater feelings of responsibility by the victim for what happened [ 25 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Finally, the results showed that the victims’ perception of violation of the law was higher among middle students than both the biennium and triennium students, consistent with greater use among younger adolescents of moral disengagement mechanisms, such as victim-blaming, resulting in greater feelings of responsibility by the victim for what happened [ 25 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 77%
“…It consists of four behavioral loci by which individuals regulate their conduct, including: justifying the behavior, shifting responsibility, minimizing the harm caused, and shifting the causal focus to the victim [ 27 ]. Moral disengagement predicts both sexual harassment and cyber-aggression by using: moral justification or diffusing responsibility to consider oneself as less responsible for one’s actions; euphemistic labeling, for example, considering these behaviors as funny or jokey; victim-blaming by attributing the responsibility to the victim, especially if the victims had sent the intimate images/videos consensually [ 25 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. With regard to moral justification, few studies have analyzed the specific mechanism of moral disengagement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were also allowed to skip any questions they did not want to answer, which resulted in men being less likely to complete the Propensity to Morally Disengage Scale (Moore et al, 2012). This may be due to social desirability, since men often score higher than women on scales of moral disengagement (Bandura et al, 1996;2001, as cited in Clemente et al, 2019Clemente et al, 2019;Pina et al, 2021), and the nature of the scale questions. While the study was anonymous, these measures were self-report, meaning there is a possibility of social desirability bias inflating or deflating scores and participants not reporting their perpetration for image-based sexual abuse or sexting coercion.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…This could be done using a scale specific to sexting coercion or image-based sexual abuse, such as the new Moral Disengagement in Image-based Sexual Abuse scale (Pina et al, 2021), which assesses moral disengagement in that specific context instead of generally. This would help researchers understand how people justify this perpetration.…”
Section: Implications and Future Directionsmentioning
confidence: 99%